GROWTH PERFORMANCE OF NATIVE CHICKEN (Gallus gallus domesticus) USING VARIED LEVELS OF WATER SPINACH (Ipomoea aquatica) LEAF MEAL AS FEED SUPPLEMENT - Kim Harold Austria Ebarle; Donabel C. Arevalo (International Journal of Multidisciplinary Research and Studies, 2023)
The study aimed to determine the effect of water spinach leaf meal (WSLM) to the growth performance of native chicken. An Experimental Research in Randomized Complete Block Design (RCBD) was used in this study of varied levels of water spinach leaf meal as feed supplement. The treatments used were as follows: during grower stage (6-14 weeks old), Treatment 1(Control)- SBM-29 kg+ WSLM- 0 kg, Treatment 2- SBM-27.5 kg+ WSLM- 1.5 kg, Treatment 3- SBM-26 kg+ WSLM- 3 kg, and Treatment 4- SBM-24.5 kg+ WSLM- 4.5 kg. And during their finisher stage (15-17 weeks old), the treatment was as follows Treatment 1(Control)- SBM-28 kg+ WSLM- 0 kg, Treatment 2- SBM-26 kg+ WSLM- 2 kg, Treatment 3- SBM-24 kg+ WSLM- 4kg, and Treatment 4- Finisher: SBM-22kg+ WSLM- 6kg. Results showed that the growth performance of native chicken such as body weight, weekly body weight, average daily gain in weight, and feed conversion ratio did not show differences among treatment means and were not affected by varied levels of water spinach leaf meal. However, average daily feed consumption had a significant effect on the 7th to 8th weeks of age only due to the water spinach’s high fiber content that led to stimulated intake. It can be concluded that varying levels of water spinach leaf meal did not affect the growth performance of native chickens. However, it can be used as cheaper alternative feed ingredients. It is also recommended to find other ways of processing of WSLM where its price can be lessened.